Estudo de sistemas em escala nanoscópica utilizando aproximação DFTB - Fernandes, Jéssica de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
In this work we investigated the physical properties of macromolecules built in common fullerene architecture, C20 and C60. The building blocks used for the geometric structuring of the porous fullerenes were the repeater units of the two-dimensional structures: graphenylene (BPC) and porous graphene (PG). We used as a method the SCC-DFTB implemented through the software package widely used for quantum simulations, the DFTB+. Thus, it was possible to perform the geometric optimization of porous molecules and structures, determine the cohesion energy of systems and investigate the electronic properties of porous fullerenes from the determination of the HOMO and LUMO frontier molecular orbitals. Furthermore, we know that, due to the high porosity of these structures, there is interest in investigating the storage of atoms and molecules inside them. Therefore, properties such as the potential barrier for the encapsulation of the H2 molecule and the Si atom were studied, as well as the adsorption of these same elements by the macromolecules.

Neste trabalho investigamos as propriedades físicas de macromoléculas construídas em arquitetura de fulerenos comuns C20 e C60. Os blocos de construção que foram utilizados para a estruturação geométricas dos fulerenos porosos foram as unidades repetidoras das estruturas bidimensionais grafenileno (BPC) e grafeno poroso (PG). Utilizamos como método o SCC-DFTB implementado através do pacote de software amplamente utilizado para simulações quânticas, o DFTB+. Assim, foi possível realizar a otimização geométrica de moléculas e estruturas porosas, determinar a energia de coesão de sistemas e investigar as propriedades eletrônicas dos fulerenos porosos a partir da determinação dos orbitais de fronteira HOMO e LUMO. Além disso, sabemos que, devido a alta porosidade dessas estruturas, há interesse na investigação do armazenamento de átomos e moléculas em seu interior. Por isso, propriedades como a barreira potencial para o encasulamento da molécula de H2 e do átomo de Silício foram estudadas, bem da adsorção desses mesmo elementos pelas macromoléculas.
Study of nanoscopic scale systems using DFTB approximation
Keywords: Porous fullerenes; Física; Simulação (Computadores); Nanoestruturas; Fulerenos porosos; Fulerenos; DFTB; DFT